Sedatives and sedation at the end of life: a nursing home retrospective cohort study. Issue Volume 12:Issue e6(2022) (28th November 2019) - Schildmann, Eva; Bolzani, Anna; Meesters, Sophie; Grüne, Bettina; Marheineke, Alina; Remi, Constanze; Bausewein, Claudia
Abstract : Objectives: Sedatives are frequently used at the end of life in specialist palliative care. There is scarce information about their use in nursing homes. Therefore, we aimed to assess the use of (1) sedatives generally and (2) 'sedatives with continuous effect', based on objective operational criteria, within the last week of life in a nursing home. Methods: This was a retrospective cohort study of residents who died in a German nursing home between 1/2015 and 12/2017, using the nursing home's medical records, which contained drug sheets and nurses' notes. Sedatives analysed were those recommended by guidelines for 'palliative sedation': benzodiazepines, levomepromazine, haloperidol (≥5 mg/day) and propofol. Exploratory statistical analysis was conducted using R V.3.6.1. Results: 46/165 (28%) deceased residents received a sedative during the last week of life, all without use of the term 'sedation'. 26/165 residents (16%) received 'sedatives with continuous effect', for median 4 days (range 1–7). Oral lorazepam was used most frequently, mainly for agitation, anxiety and dyspnoea, but also due to palliative status and patients wish. The median total daily dose of lorazepam within the last week of life was 1.5 mg (range 0.5–7.5). The term 'palliative' was significantly more often used for residents receiving sedatives (p=0.001). Conclusions: Compared with published data on continuous deep sedation, moderate or deep sedation was less frequent in this nursing home and never labelled as 'sedation'. Multicentre mixed-methods research is needed to gain representative and more detailed data on sedation practices at the end of life in nursing homes.